Methylpalladium complexes with pyrimidine-functionalized N-heterocyclic carbene ligands - Meyer, Dirk; Strassner, Thomas (Beilstein Journal of Organic Chemistry, 2016)
A series of methylpalladium(II) complexes with pyrimidine-NHC ligands carrying different aryl- and alkyl substituents R ([((pym)^(NHC-R))PdII(CH3)X] with X = Cl, CF3COO, CH3) has been prepared by transmetalation reactions from the corresponding silver complexes and chloro(methyl)(cyclooctadiene)palladium(II). The dimethyl(1-(2-pyrimidyl)-3-(2,6-diisopropylphenyl)imidazolin-2-ylidene)palladium(II) complex was synthesized via the free carbene route. All complexes were fully characterized by standard methods and in three cases also by a solid state structure.
Keywords: alkane activation; alkyl complex; NHC; palladium; solid state structure